2009
DOI: 10.1370/afm.999
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Antibiotics for Purchase Without a Prescription on the Internet

Abstract: PURPOSE Reducing inappropriate use of antibiotics is key to many antibiotic resistance initiatives. Most initiatives, however, focus almost exclusively on controlling prescribing by health care clinicians and do not focus on patient selfmedication. The purpose of this study was to examine antibiotics available to patients without a prescription, a phenomenon on the Internet. METHODSWe conducted an Internet search using 2 major search engines (Google and Yahoo) with the key words "purchase antibiotics without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 24 publications
3
63
1
1
Order By: Relevance
“…Furthermore, from subjects that experienced self medication with antibiotics including amoxicillin, ampicillin, fradiomicyn-gramicidin, ciprofloxacin and tetracycline, those antibiotics were used to treat minor diseases such as common cold, cough and fever [14]. A recent study from Mainous et al [16] have highlighted that currently antibiotics are freely available for purchase on the Internet without a prescription, thus encouraging selfmedication and low quality of care.…”
mentioning
confidence: 99%
“…Furthermore, from subjects that experienced self medication with antibiotics including amoxicillin, ampicillin, fradiomicyn-gramicidin, ciprofloxacin and tetracycline, those antibiotics were used to treat minor diseases such as common cold, cough and fever [14]. A recent study from Mainous et al [16] have highlighted that currently antibiotics are freely available for purchase on the Internet without a prescription, thus encouraging selfmedication and low quality of care.…”
mentioning
confidence: 99%
“…Mainous et al fi nd that antibiotics are widely available on the Internet without prescription. 7 Given the unregulated nature of the Internet, these fi ndings may have serious implications for patient health, quality of care, and efforts to reduce antibiotic resistance.…”
Section: A Social and Cultural Lensmentioning
confidence: 99%
“…I n follow-up to a study showing the wide availability of antibiotics without prescription via the World Wide Web, 1 Mainous and colleagues found that a year-long multimedia campaign did not decrease the high incidence of acquiring antibiotics without a prescription among Latinos in a South Carolina community. 2 Immigrants who had bought antibiotics without prescription in their home country were likely to continue this practice in the United States.…”
mentioning
confidence: 99%